Perception of Acceptance and Discrimination Among the LGBTQI + Community in their Churches and its Association with Spiritual Dryness: Findings from a Cross-Sectional Study in Germany - Büssing, Arndt (Journal of religion and health, 2024)
Data from a cross-sectional survey with options for free text statements revealed that people who identify themselves as part of the LGBTQI+ community (n = 417) experienced both acceptance and discrimination by church members. Their negative experiences affected their relationship with God in terms of spiritual dryness and loss of faith. In regression analyses, the best predictors of life satisfaction and psychological well-being were self-acceptance and low spiritual dryness. This self-acceptance as a resource, mediated the link between spiritual dryness and life satisfaction. Nevertheless, 96% still wish for a church/faith community that welcomes all people—and accepts them as they are and feel.